Every good boy does fine : a love story, in music lessons - Denk, Jeremy (Random House, 2022)
"In this searching and funny memoir, based off his popular New Yorker article, renowned pianist Jeremy Denk traces an implausible journey. Life is difficult enough as a precocious, temperamental, and insufferable six-year-old piano prodigy in New Jersey. But then a family meltdown forces a move to New Mexico, far from classical music's nerve centers, and he has to please a new taskmaster while navigating cacti, and the perils of junior high school. Escaping from New Mexico at last, he meets a bewildering cast of college music teachers, ranging from boring to profound, and experiences a series of humiliations and triumphs, to find his way as one of the world's greatest living pianists, a MacArthur "Genius," and a frequent performer at Carnegie Hall. There are few writers working today who are willing to eloquently explore both the joys and miseries of artistic practice. Hours of daily repetition, mystifying early advice, pressure from parents and teachers who drove him on-an ongoing battle of talent against two enemies: boredom and insecurity. As we meet various teachers, with cruel and kind streaks, Denk composes a fraught love letter to the act of teaching. He brings you behind the scenes, to look at what motivates both student and teacher, locked in a complicated and psychologically perilous relationship. In his imaginative prose, Denk explores how classical music is relevant to "real life," despite its distance in time. He dives into pieces and composers that have shaped him-Bach, Mozart, Schubert, and Brahms, among others-and gives unusual lessons on melody, harmony, and rhythm. Why and how do these fundamental elements have such a visceral effect on us? He tries to sum up many of the lessons he has gotten, to repay the debt of all his amazing teachers; to remind us that music is our creation, and that we need to keep asking questions about its purpose"--